3D Pine‐Needle‐Like W18O49/TiO2 Heterostructures as Dual‐Band Electrochromic Materials with Ultrafast Response and Excellent Stability. Issue 7 (22nd February 2022) - Huang, Ya; Wang, Baoshun; Bai, Xiaojuan; Han, Ying; Zhang, Wenshuo; Zhou, Chenhui; Meng, Haibing; Chen, Fengxiang; Wu, Xueke; Jiang, Qinyuan; Li, Run; Zhang, Shiliang; et al.
Abstract: Dual‐band electrochromic (EC) smart windows, which can selectively modulate visible (VIS) and near‐infrared (NIR) light are widely regarded as one of the most attractive options to drastically reduce energy consumption in modern buildings. However, dual‐band EC smart windows still face many challenges such as weak modulation selectivity between VIS and NIR bands, low switching speed, poor durability, and high cost. Here, inspired by pine needles, a unique pine‐needle‐like (PNL) W18 O49 /TiO2 heterostructure is rationally constructed with W18 O49 nanothorns (as branches) and TiO2 nanofibers (as backbones). The PNL‐W18 O49 /TiO2 heterostructures exhibit superior dual‐band EC performance in both VIS and NIR bands, which can block up to 81.4% of the VIS light at 633 nm and 91.3% of NIR at 1800 nm, and they also show extremely short bleaching/coloring time (0.9/1.2 s) and excellent stability (85% of capacity retention after 20 000 cycles) in a narrow potential window of −0.8 to 0.6 V. Besides, abundant patterned EC layers on a fluorine‐doped‐tin‐oxide‐coated conductive glass and flexible polyester conductive films can also be realized. This work provides an effective way for dual‐band EC materials' design and their further development in smart windows and intelligent displays. Abstract : The 3D pine‐needle‐like W18 O49 /TiO2 heterostructure network with increased specific surface area and more active sites exhibits a dual‐band electrochromic (EC) ability, fast response speed, and excellent cycling stability in a narrow potential window. Additionally, it is easy to be patterned with different masks which shows the potential in dual‐band EC smart windows and intelligent displays.